Port-Site Metastasis (PSM): Definition, clinical contexts and possible preventive actions to reduce risk - Giulio Perrotta (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
The "port-site metastasis" represents a tumor recurrence that develops in the abdominal wall within the scar tissue of the insertion site of one or more trocars, after laparoscopic surgery, not associated with peritoneal carcinomatosis. This last aspect is central because in the literature some isolated cases are reported, but most cases are associated with peritoneal carcinomatosis. The first case in the literature dates back to 1978 and in the literature, the incidence varies from 1% to 21%, although most published research reports a very small number of patients. Currently, the incidence in a specialized cancer center is consistent with the incidence of recurrence on a laparotomy scar. Possible mechanisms for cell implantation at the port site are direct implantation into the wound during forced, unprotected tissue retrieval or from contaminated instruments during tumor dissection; the effect of gas turbulence in lengthy laparoscopic procedures, and embolization of exfoliated cells during tumor dissection or hematogenous spread. Probably, however, the triggering mechanism is necessarily multifactorial. To date, the only significant prognostic factor in patients diagnosed with port-site metastasis is the interval between laparoscopy and the diagnosis of the port site: in fact, patients who develop the port site within 7 months after surgery have a generally worse prognosis, as well as port-site metastasis are more frequent in advanced cancers and the presence of ascites. To reduce the risk, the following measures are proposed in the literature: 1) Select the patient who does not have a metastatic oncologic condition or friable cancerous masses or lymph node spread or attached external or intracystic vegetations, preferring well-localized, benign or low-malignant or otherwise intact tumors; 2) Use wound protectors and use of protective bags (or endo bag) for tissue retrieval; 3) Peritoneal washing with heparin, to prevent free cell adhesion, or washing with cytocidal solutions. Evaluate the utility of using Povidone-iodine, Taurolidine (which has anti-adhesion activity and decreases proangiogenic factors), and chemotherapy products; 4) Avoid removing pneumoperitoneum with trocars in place; 5) Avoiding direct contact between the solid tumor and the port site; 6) Prefer laparoscopy to laparotomy, if possible; 7) Avoid the use of gas or direct CO2 insufflation, although in literature the point is controversial and deserves more attention and study, as the initial hypothesis that CO2 increased the invasion capacity of tumor cells (in vitro and in vivo) has been refuted several times. Insufflation of hyperthermic CO2 and humidified CO2 leads to a better outcome in patients with a malignant tumor who undergo a laparoscopic procedure compared with normal CO2 pneumoperitoneum; 8) Comply with surgical protocols and techniques by updating one's surgical skills, as it has been demonstrated, as already reported here, the presence of cancerous cells on instruments, washing systems and trocars (in particular, on the trocars of the first operator). Suturing all layers of the abdominal wall decreases the risk of the port site; 9) Avoid excessive manipulation of the tumor mass during the surgical/operative procedure.